Demographic, medical, and financial statistics from the Jaffna Jaipur Centre for Disability Rehabilitation (JJCDR) database, 1987-2018: a prosthetics, orthotics, and mobility clinic in northern Sri Lanka - Michael Berthaume; Spencert Barnes; Shehan Hettiaratchy; Jon C Clasper; Ahilakumar Kumar; Gitanjali Sathiadas; Jeya Ganeshamoorthy (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background When dealing in global health, it is crucial to have a comprehensive understanding of community demographics and needs. From 1983-2009, a 26-year ethnic civil conflict devastated Sri Lanka, disproportionately affecting people living in the north and creating a large amputee population. Here, we use routinely collected prosthetic and orthotic data to investigate the composition of the amputee community in northern Sri Lanka. # Methods The Jaffna Jaipur Centre for Disability Rehabilitation (JJCDR) was established in 1987 and has been the only centre consistently providing prosthetic, orthotic, and non-orthopaedic services in northern Sri Lanka spanning during and after the civil war. In 2004, with the help of the charity Motivation, they established an electronic patient database, which records and maintains information on the JJCDR's patients. An anonymized copy of the JJCDR database was obtained in November 2018. Summative statistics and temporal trends in patient data were investigated. # Results 3,665 unique patients registered with the JJCDR from 1986-2018 (2,605 male, 1,060 female). Individuals ranged from 0-90 years old, with a mean/median age of 34.76/32 years old. Key findings include: (i) 93.0% patients with amputation site recorded were lower limb amputees, with 74.3% being transtibial amputees; (ii) The majority of patients with cause of amputation recorded had war-related amputations (61.2%); (iii) diabetes was the highest cause for non-war-related amputations (18.3%); (iv) war-related amputations have ceased, while diabetic amputations are on the rise; and (v) peak recorded financial costs due to prosthetic and orthotic (P&O) creation/maintenance occurred in 2013, 4 years after the war ended. # Conclusions These analyses provide crucial insight into the P&O population in northern Sri Lanka, including distribution and frequency for causes/sites of amputations, temporal patterns in causes of amputations, and costs to a P&O centre due to device creation and maintenance. This database and analysis provide invaluable insight into the P&O cohort in northern Sri Lanka, and a unique insight into the P&O needs of a post-conflict LMIC from the perspective of a P&O centre.